Pneumocephalus following Lumbar Spine Surgery: A Rare Cause of Delayed Emergence from Anesthesia - Lamsal, Ritesh; Mishra, Rajeeb K.; Kumar, Niraj (Journal of Neuroanaesthesiology and Critical Care, 2018)
Pneumocephalus is an unusual presentation after lumbar spine surgery. We report the case of a young healthy patient, who had delayed emergence from anesthesia after undergoing an uncomplicated lumbar spine surgery. After shifting to the Intensive Care Unit, the patient had an episode of generalized tonic—clonic seizure. Computed tomography scan revealed the presence of pneumocephalus. The patient was managed conservatively, extubated the following day and discharged with no neurological deficits.
Keywords: delayed emergence; lumbar spine; pneumocephalus